2020
DOI: 10.1002/ecy.3007
|View full text |Cite
|
Sign up to set email alerts
|

Alternative designs and tropical tree seedling growth performance landscapes

Abstract: The functional trait values that constitute a whole-plant phenotype interact with the environment to determine demographic rates. Current approaches often fail to explicitly consider trait 9 trait and trait 9 environment interactions, which may lead to missed information that is valuable for understanding and predicting the drivers of demographic rates and functional diversity. Here, we consider these interactions by modeling growth performance landscapes that span multidimensional trait spaces along environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 78 publications
0
54
0
Order By: Relevance
“…Potential reasons explaining the allocation response to soil P include: first, it is possible that plant responses to resource heterogeneity may involve shifts in other traits, that compensate for the lack of variation in these biomass allocation traits (Reich et al, 1998;Santiago et al, 2004;Worthy et al, 2020). In fact, we showed that the PC1 can better capture responses to soil P by describing significant increase in non-photosynthetic tissues (e.g.…”
Section: Biomass Allocation Trade-offs In Response To Light and Soimentioning
confidence: 86%
“…Potential reasons explaining the allocation response to soil P include: first, it is possible that plant responses to resource heterogeneity may involve shifts in other traits, that compensate for the lack of variation in these biomass allocation traits (Reich et al, 1998;Santiago et al, 2004;Worthy et al, 2020). In fact, we showed that the PC1 can better capture responses to soil P by describing significant increase in non-photosynthetic tissues (e.g.…”
Section: Biomass Allocation Trade-offs In Response To Light and Soimentioning
confidence: 86%
“…With the inclusion of three‐way interactions between two traits and one environment, Worthy et al . (2020) found alternative functional designs and multiple growth peaks and they shifted along environmental gradients. In our study, we found multiple performance peaks, not only for growth but also for survival, in a few models with significant three‐way and four‐way interactions (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, Worthy et al . (2020) is the only example to date that has empirically tested higher‐order trait × trait × environment interactions and found evidence of alternative designs and multiple growth performance peaks. That study did not consider other performance metrics besides growth nor the multidimensional nature of the environment.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, local species composition should cover a relatively narrow range of trait values that fit the requirements of the environment there. However, this expectation contradicts the often‐observed pattern of a wide diversity of forms and functions in tropical plant communities and suggests the existence of alternative phenotypes with equivalent performance (Marks and Lechowicz 2006, Worthy et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively to these two scenarios, traits might not be strongly optimized toward a single or a narrow range of values. Instead, plants may display contrasting phenotypes that constitute alternative solutions for the given local conditions (Marks and Lechowicz 2006, Muscarella and Uriarte 2016, Worthy et al 2020). For example, Hirose and Werger (1995) found that in a tropical forest different species of trees exhibit contrasting strategies for capturing light that result in similar performance.…”
Section: Introductionmentioning
confidence: 99%